Penerapan Metode Forward Chaining Pada Sistem Pakar Diagnosa Penyakit Ayam Ternak - Ahmad Januar Amriyansah; Heni Sulistiani; Riska Amalia (LPPM STIKI MALANG, 2024)
One of the most serious problems faced by chicken farmers is chicken disease. Chicken diseases can be diagnosed by identifying the symptoms that appear and also consulting with an expert. However, this method requires a long time and is quite expensive. Therefore, this research aims to implement the forward chaining method in an expert system to help chicken farmers in diagnosing chicken diseases online. This expert system was developed using the PHP programming language and MySQL database. This expert system also provides treatment guidelines that are in accordance with the diagnosed disease. The expert system was tested using 33 symptoms and 10 common chicken diseases. The test results show that this expert system can diagnose chicken diseases with high accuracy and provide diagnosis results directly through a web browser. This expert system can also improve users' understanding of website creation and chicken diseases.